2010
DOI: 10.1096/fj.10-166272
|View full text |Cite
|
Sign up to set email alerts
|

α-Conotoxin BuIA[T5A;P6O]: a novel ligand that discriminates between α6β4 and α6β2 nicotinic acetylcholine receptors and blocks nicotine-stimulated norepinephrine release

Abstract: α6* (asterisk indicates the presence of additional subunits) nicotinic acetylcholine receptors (nAChRs) are broadly implicated in catecholamine-dependent disorders that involve attention, motor movement, and nicotine self-administration. Different molecular forms of α6 nAChRs mediate catecholamine release, but receptor differentiation is greatly hampered by a paucity of subtype selective ligands. α-Conotoxins are nAChR-targeted peptides used by Conus species to incapacitate prey. We hypothesized that distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 65 publications
(40 reference statements)
1
89
0
Order By: Relevance
“…1B. However, structure-function studies of ␣-Ctxs MII (McIntosh et al, 2004), PnIA (Hogg et al, 1999;Luo et al, 1999), and BuIA (Azam et al, 2010) suggested that PeIA would be a promising platform from which to develop ␣6␤2-selective ligands. These studies demonstrated that specific amino acids of MII confer high potency for the ␣6/␣3␤2␤3 subtype and that the 10th position in PnIA is critical for subtype selectivity and provided a rational strategy for engineering ␣6/␣3␤2␤3 subtype-selective ligands using PeIA as a template.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B. However, structure-function studies of ␣-Ctxs MII (McIntosh et al, 2004), PnIA (Hogg et al, 1999;Luo et al, 1999), and BuIA (Azam et al, 2010) suggested that PeIA would be a promising platform from which to develop ␣6␤2-selective ligands. These studies demonstrated that specific amino acids of MII confer high potency for the ␣6/␣3␤2␤3 subtype and that the 10th position in PnIA is critical for subtype selectivity and provided a rational strategy for engineering ␣6/␣3␤2␤3 subtype-selective ligands using PeIA as a template.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other areas such as the retina (Moretti et al, 2004;Marritt et al, 2005) and the locus ceruleus (Léna et al, 1999;Vincler and Eisenach, 2003;Azam and McIntosh, 2006), ␣6␤4* nAChRs are present and may be coexpressed with the ␣6␤2* subtype. Moreover, in the hippocampus of mouse, ␣6␤4* nAChRs control the release of norepinephrine (Azam et al, 2010). Last, in the peripheral nervous system, ␣6␤4* nAChRs are expressed by human adrenal chromaffin cells (Pé rez-Alvarez et al, 2012) and by rat dorsal root ganglion neurons (Hone et al, 2012), two cell populations that also have substantial ␤2 subunit expression.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have identified the ␣6␤2␤3 and ␣6␣4␤2␤3 subtypes localized on dopaminergic neurons in the substantia nigra and ventral tegmental area as key modulators of dopamine release in striatum and nucleus accumbens (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), making the receptors interesting in connection with Parkinson disease and nicotine addiction (4,6,17). Although not having been subjected to the same meticulous exploration as ␣6␤2* receptors, ␣6␤4* nAChRs have recently been reported to regulate norepinephrine release in mouse hippocampus (18), to play a major role for exocytosis in human adrenal gland chro-* This work was supported by the Lundbeck Foundation, The Aase and Ejner maffin cells (19), and to be expressed in rat dorsal root ganglia (20).…”
mentioning
confidence: 99%
“…However, they seem capable of integrating as "accessory" subunits into complexes containing at least one other ␣ and one other ␤ subunit. ␣6*-nAChR (where the * indicates the known or possible presence of additional subunits in the complex) are expressed in the mammalian brain, predominantly in dopaminergic midbrain regionsimplicatedinpleasure,reward,anddrug(includingnicotine) dependence; they modulate dopamine release and could be involved in schizophrenia and Parkinson disease (2)(3)(4)(5)(6)(7). nAChR ␣6 and ␤3 subunit messages share very similar expression patterns, and studies using knock-out animal and ␣-conotoxin sensitivity assessments suggest that ␤3 subunit incorporation is important in the assembly and stability of mature ␣6*-nAChR, which also must have channel functions.…”
mentioning
confidence: 99%
“…Mammalian ␣6*-nAChR are thought to naturally exist as combinations of ␣6 with ␤2 alone or with addition of ␤3 subunits and perhaps of ␣6 and ␤4 subunits (1,7). However, nAChR with these subunit compositions are not easily recreated in functional forms in artificial expression systems (8).…”
mentioning
confidence: 99%